Investing in leadership and empowerment: A practical roadmap to maximize Employee performance - Haryoto, Cecep Yoto (Greenation International Journal of Tourism and Management, 2023)
The purpose of this research is to know and analyze: (1) Leadership (2) Empowerment; (3) Performance; and (4) The influence of Leadership and Empowerment on the performance of Employees of PT Citra Teknik Medika Bandung City, either simultaneously or partially. The research method used in this study was a descriptive survey and an explanatory survey. The unit of analysis in this study were employees of PT Citra Teknik Medika, Bandung, with a sample of 33 people. The type of investigation is causality, and the time horizon in this study is cross-sectional. Based on the results of the study, it was found that leadership according to PT Citra Teknik Medika Bandung City Employees, it turned out that most Employees gave quite good responses, Empowerment to PT Citra Teknik Medika Bandung City Employees in general can be said to be not good, Performance of PT Citra Teknik Medika Bandung City Employees when this is considered good. Leadership and Empowerment simultaneously affect the performance of Employees of PT Citra Teknik Medika Bandung City. However, partially dominant leadership affects performance rather than empowerment. Because Empowerment is more dominant in influencing performance, it is the first priority in improving performance. then employees of PT Citra Teknik Medika Bandung City are advised to remain consistent in participating in the empowerment that is being held, so that they are able to work more professionally.